I. A Conversation on The Wisdom of Religious Commitment by Terrence W. Tilley - Downey, John K. (Philosophy & theology, 1997)
Tilley argues that since religions are not summaries of bloodless beliefs but embodied communal practices, the heuristic for the justification of beliefs must shift. Although some of the lines of this shift to practical wisdom remain vague, Tilley has taken philosophy of religion in an excellent direction. Attention to these questions would sharpen his sketch: Why abandon linguistic philosophy with no attention to the help one might receive from the embodied linguistic practice of the later Wittgenstein? What grounds the wisdom we seek to practice? Can community outsiders argue with insiders? Do these embodied philosophical arguments differ from theological arguments?